Analysis of Canva Utilization in Art Learning Activities of Grade V Students at SD Negeri 3 Palu - Wahyu Pratama Makasau; Andi Imrah Dewi; Kadek Hariana; Zulnuraini Zulnuraini; Andi Rahmaeni (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to analyze the implementation of Canva utilization in Art learning activities and to identify supporting and inhibiting factors among Grade V students at SD Negeri 3 Palu. This research employed a qualitative, descriptive approach. Data were collected through observation, interviews, and documentation involving one teacher and 32 students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results show that the implementation of Canva was carried out systematically through interactive demonstrations using Canva features and direct group practice. The use of Canva increased students’ motivation, creativity, and engagement in producing digital artworks. Students were able to explore ideas more freely and express their imagination through various design features provided by the application. Supporting factors included the availability of adequate devices, students’ interest in technology-based learning, and collaborative learning through peer interaction. Meanwhile, inhibiting factors included limited digital literacy among some students, unstable internet connections, and limited time allocation during the learning process. In conclusion, the integration of Canva successfully created a more interactive and meaningful learning experience, while also enhancing students’ creativity and digital skills relevant to 21st-century learning.